Pengaruh model pembelajaran guided inquiry terhadap kemampuan pemahaman konsep matematis siswa kelas X SMAN 2 Rambah Hilir - Syahfitri, Ely; Nurrahmawati; Arcat (Jurnal Pendidik Indonesia, 2023)
The student's ability to comprehend mathematical concepts remains a primary concern that needs improvement. This issue often arises due to the dominant role of teachers in the learning process, which can lead students to become passive. This research investigates the impact of using the Guided Inquiry instructional model on students' mathematical concept comprehension. The research method employed is quasi-experimental, involving 10th-grade students at SMAN 2 Rambah Hilir as the population. Sample selection was done using the simple random sampling method, resulting in two student groups: class X.B as the control group and class X.E as the experimental group. Data were collected through a specially designed test technique to measure students' mathematical concept comprehension. The test instrument underwent validation, difficulty level analysis, discrimination power assessment, and reliability analysis. Data analysis was performed using the Mann-Whitney statistical test, yielding a calculated zscore of 4.67, while the critical ztable value was 1.96. These results indicate that the calculated zscore > critical ztable value indicates a significant positive impact of implementing the Guided Inquiry model on the mathematical concept comprehension of 10th-grade students at SMAN 2 Rambah Hilir.